2017
DOI: 10.1007/s10212-017-0342-0
|View full text |Cite
|
Sign up to set email alerts
|

Training peer-feedback skills on geometric construction tasks: role of domain knowledge and peer-feedback levels

Abstract: Training peer-feedback skills on geometric construction tasks: role of domain knowledge and peer-feedback levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 42 publications
0
52
2
2
Order By: Relevance
“…For example, with greater experience, peers tend to use scoring criteria to a greater extent (Sluijsmans et al 2004). Similarly, training peer assessment over time can improve the quality of feedback they provide, although the effects may be limited by the extent of a student's relevant domain knowledge (Alqassab et al 2018). Frequent peer assessment may also increase positive learner perceptions of peer assessment (e.g., Sluijsmans et al 2004).…”
Section: Frequencymentioning
confidence: 99%
“…For example, with greater experience, peers tend to use scoring criteria to a greater extent (Sluijsmans et al 2004). Similarly, training peer assessment over time can improve the quality of feedback they provide, although the effects may be limited by the extent of a student's relevant domain knowledge (Alqassab et al 2018). Frequent peer assessment may also increase positive learner perceptions of peer assessment (e.g., Sluijsmans et al 2004).…”
Section: Frequencymentioning
confidence: 99%
“…Various training methods for giving (peer) feedback have been developed and studied. In general, these training methods include a variety of instructional scaffolds, such as learning new theory about feedback (Voerman et al 2015), studying worked examples of feedback (Alqassab et al 2018;Sluijsmans et al 2002), observing models which demonstrate how to give feedback (Van Steendam et al 2010), following a structured format for giving feedback (Gielen and De Wever 2015), defining assessment criteria (Sluijsmans et al 2002), following instructions to use received feedback actively (Gielen et al 2010;Wichmann et al 2018), and receiving expert feedback on feedback provided to others (Voerman et al 2015).…”
Section: Preparing Students For Giving Feedbackmentioning
confidence: 99%
“…Some studies have tested the combined effect of various instructional scaffolds in a holistic way. Several of these studies found positive effects of peer feedback training on students' feedback skills (Alqassab et al 2018;Sluijsmans et al 2002;Voerman et al 2015). For instance, Sluijsmans et al (2002) developed a training program in which undergraduate students defined assessment criteria, gave peer feedback, studied examples of expert feedback, and learned how to write a feedback report.…”
Section: Preparing Students For Giving Feedbackmentioning
confidence: 99%
“…The students' domain knowledge influences the reliability and the style of feedback given (Alqassab, Strijbos & Ufer, 2018;Van Zundert et al, 2012). Hence, the students' strength of mathematical knowledge influences the quality and the reliability of the feedback given.…”
Section: Discussionmentioning
confidence: 99%